A crypto-tourism case study of agnes water/seventeen seventy, Australia. (January 2023) - Chen, Shu-Hsiang (Ava); Tham, Aaron
This research note explores the under-investigated assumption that cryptocurrencies are a panacea to stimulate regional tourism demand. Through the application of Rogers' Diffusion of Innovation Theory, a case study was designed to examine the cryptocurrency effect on two adjacent towns of Agnes Water and 17 70 in Central Queensland, Australia. The findings revealed three major factors that led to merchant receptivity for adopting cryptocurrencies - First, a novelty effect perceived as a good strategy to induce consumer spend. Second, the low entry barriers for merchants adopting cryptocurrencies to conduct transactions. Third, cryptocurrencies incurred zero overhead costs. Nevertheless, the favorable attitudes of these merchants towards cryptocurrencies require a demand-side intention to use such tools during tourist visits to these regional destinations. Other regional tourism destinations will need to consider other ways of integrating such digital innovations to their landscapes.